Well-being during a time of change : Timor-Leste on the path to independence - Richter, Kaspar (Policy research working paper, 2005)
"Countries undergoing fundamental economic and political transformations might experience differential adjustments in material well-being and empowerment. Richter evaluates self-rated welfare and power changes in Timor-Leste covering the period prior to the 1999 referendum on independence from Indonesia to the eve of independence in end 2001. Drawing on the first nationally representative household survey and village census, he shows how subjective, objective, and recall information can be combined to provide a rich profile of trends in well-being from the pre- to post-conflict stage. The author's analysis shows that changes in self-rated welfare and power broadly corresponded to changes recorded by objective indicators. While economic well-being improved little, empowerment increased dramatically. The changes were not uniform across the population but some groups benefited more than others. The evidence for Timor-Leste is consistent with these hypotheses: * Economic resources increase welfare, and more than power. * Social resources increase power, and more than welfare. * Welfare winners have low initial economic resources. * Power winners have high social resources. * Economic shocks reduce welfare and power, but welfare more than power. This paper--a product of the Poverty Reduction and Economic Management Sector Unit, East Asia and Pacific Region--is part of a larger effort in the region to promote economic research on small countries"--World Bank web site